Leadership, teams, and collaborative groups – its relationship with job satisfaction - Pérez Vilar, Pablo Sebastián (2013)
Results obtained from a literature review of scientific articles related to job satisfaction published between the years 2000 and 2010, are presented. Findings of research studies analyzed indicate the relationship between leadership, some aspects of the supervision, groups, teams and its influence on job satisfaction. The revised bibliography noted mainly the positive relationship between transformational leadership and the SWA model of supervision on job satisfaction. Also the importance of the influence of certain aspects such as the efficacy group, group cohesion and the need to share values for group work be more satisfying than individual work.